Synthesis method of high-performance polyimide binder with three-dimensional network structure
Through the polymerization reaction of dianhydride and diamine combined with the crosslinking of tannin acid, a polyimide binder with a three-dimensional network structure is formed, which solves the problems of complex and insufficient performance of polyimide synthesis in the prior art, and achieves the efficient synthesis of high-performance polyimide materials and excellent mechanical and thermal stability.
Patent Information
- Application Number
- CN202411990840.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
The existing polyimide synthesis methods are complex and difficult to achieve high molecular weight, resulting in insufficient mechanical strength and toughness of the material, especially in high-temperature environments, and the post-processing process is complex, affecting the purity and performance of the material.
The polymerization reaction of dianhydride and diamine combined with crosslinking of tannin acid is adopted to achieve efficient synthesis of high-performance polyimide materials through a three-dimensional network structure polyimide binder synthesis method.
It improves the mechanical strength and toughness of polyimide materials, enhances tensile and compressive resistance, improves thermal stability and stability to solvents and chemical reagents, and extends service life.
Smart Images

Figure CN119709104A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, in particular to a method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure. Background Art
[0002] Polyimide is a class of polymer materials with excellent functional properties. It is widely used in electronics, aerospace, automobiles and other fields, especially in high temperature and high performance environments.
[0003] In recent years, with the growing demand for high-performance materials, the synthesis methods for polyimide have been continuously developed. However, the existing polyimide synthesis methods, such as chemical synthesis and thermal curing, usually involve complex reaction steps and condition control, which increases the technical difficulty and experimental cost of the synthesis process; many traditional polyimide synthesis methods may not be able to achieve the synthesis goal of high molecular weight polyimide, which leads to insufficient mechanical strength and toughness of the final material, especially the mechanical properties are prone to decrease under high temperature environment. Therefore, the application of polyimide synthesized by these methods under high pressure and high temperature conditions is limited; and in the existing methods, the post-treatment process of polyimide is usually complicated, and it is difficult to remove unreacted monomers, catalysts or solvents. This not only affects the purity of the final material, but may also have a negative impact on the performance of the polyimide. Additional washing and drying steps are required during the treatment process, which increases the complexity and time cost of the production process.
[0004] To this end, those skilled in the art have proposed a method for synthesizing a high-performance polyimide binder with a three-dimensional network structure, aiming to utilize the polymerization reaction of dianhydride and diamine combined with the cross-linking of tannic acid to achieve the efficient synthesis of high-performance three-dimensional network structure polyimide. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure to solve the problems raised in the background technology.
[0006] A method for synthesizing a high-performance polyimide binder with a three-dimensional network structure comprises the following steps:
[0007] S1, preparing a high molecular weight polyimide by reacting dianhydride and diamine, and using the polyimide as a matrix to provide a chain-like support;
[0008] S2, dissolving polyimide in N,N-dimethylformamide solvent to obtain a polyimide solution;
[0009] S3, selecting tannic acid as a cross-linking agent, dissolving the tannic acid in deionized water to form a tannic acid solution, and slowly adding the solution to the polyimide solution under stirring to mix thoroughly;
[0010] S4, cross-linking the polyimide solution with the tannic acid solution to form a product with a three-dimensional grid structure;
[0011] S5. After the reaction is completed, the product is post-treated, the product is washed to remove unreacted tannic acid and solvent, and then dried to obtain the final polyimide adhesive.
[0012] Preferably, in step S1, dianhydride and diamine are used as raw materials, wherein the dianhydride includes one or more of terephthalic dianhydride, phthalic dianhydride and maleic dianhydride, and the diamine includes one or more of p-phenylenediamine, diaminobenzene and diaminobenzimidazole;
[0013] In a dry reaction container, dianhydride and diamine monomers are respectively dissolved in N,N-dimethylformamide solvent, the monomer concentration is between 0.5-2.0 mol / L, and pyridine is added as a catalyst to carry out polymerization reaction.
[0014] Preferably, when the dianhydride solution and the diamine solution are subjected to polymerization reaction, the diamine solution is slowly added to the dianhydride solution under nitrogen protection, while stirring, and the temperature is maintained between 200-250° C. During the reaction, the polymer chain gradually grows, and the monomer concentration gradually decreases. After the reaction is completed, the solution is cooled to room temperature, and the obtained reaction product presents a high-viscosity solution or gel state;
[0015] The reaction product is poured into a cold ethanol solvent to precipitate polyimide, and the reaction product is washed with the cold ethanol solvent for multiple times to remove any unreacted monomers or residual solvents, and then the product is dried by vacuum drying until a constant weight state is obtained to obtain a high molecular weight polyimide as a matrix material.
[0016] Preferably, in step S2, the synthesized high molecular weight polyimide is pre-crushed and gradually added into an N,N-dimethylformamide solvent, and the polyimide and the solvent are mixed by stirring at a low speed using a magnetic stirrer until the polymer is completely dissolved to obtain a polyimide solution;
[0017] During the stirring process, gentle heating is carried out and the temperature is maintained between 40-60°C.
[0018] Preferably, in step S3, the tannic acid powder is slowly added to 100-200 mL of deionized water in batches, and a magnetic stirrer is used to continuously stir at a medium speed to allow the tannic acid to fully contact the deionized water, and the dissolution process is carried out at room temperature for 10-30 minutes until the tannic acid is completely dissolved to form a clear tannic acid aqueous solution;
[0019] Under stirring conditions, slowly add the tannic acid solution to the polyimide solution, use a pipette or dropper to control the addition speed, and continue stirring during the addition process to fully mix the tannic acid solution and the polyimide solution. Keep the temperature at room temperature and the mixing time is 30 minutes to 1 hour.
[0020] Preferably, in step S4, sodium hydroxide solvent is added dropwise to the fully mixed polyimide and tannic acid solution, and the mixed solution is heated to 150-200° C. and stirred to allow the reactants to fully contact and react, and the reaction time is 2-4 hours;
[0021] Under the conditions of heating and stirring, the tannic acid molecules react with the functional groups on the polyimide chains to form cross-linked bonds, which connect the polyimide chains together to form a three-dimensional network structure.
[0022] Preferably, in step S5, after the cross-linking reaction reaches a predetermined degree, the reaction container is moved from the heating source to room temperature, the reaction is stopped by lowering the temperature, and after the temperature is lowered to room temperature, the stirring is stopped to obtain a polyimide gel product;
[0023] The cross-linked polyimide gel is washed with ethanol to remove unreacted tannic acid, catalyst and other impurities. During the washing process, ethanol is added to the container to completely immerse the product, and gently stirred with a glass rod or a magnetic stirrer to allow the solvent to fully contact the polyimide surface. The washing time is 30 minutes to 1 hour, and the washing is repeated 2-3 times until the pH value or color of the washing solution is close to neutral;
[0024] The washed polyimide product is transferred to a drying container and vacuum dried to obtain a final polyimide adhesive.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The high molecular weight polyimide synthesized by the polymerization reaction of dianhydride and diamine is used as the matrix material, which provides good mechanical strength and toughness. The three-dimensional network structure formed by the associated reaction significantly enhances the strength and rigidity of the material and improves its tensile and compressive resistance.
[0027] 2. The polyimide material of the present invention has good thermal stability and is suitable for use in high temperature environments. It can maintain its performance at temperatures up to 300°C. The cross-linking reaction further improves the thermal stability of the material and reduces the risk of thermal degradation, making it suitable for high temperature applications. The cross-linking effect of tannic acid enhances the material's stability to solvents and chemical reagents, thereby extending its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1The present invention is a flow chart of the synthesis method of the polyimide adhesive. DETAILED DESCRIPTION
[0029] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0030] As attached Figure 1 As shown:
[0031] Embodiment: The present invention provides a method for synthesizing a high-performance polyimide binder with a three-dimensional network structure, comprising the following steps:
[0032] S1, using dianhydride and diamine to react to prepare a high molecular weight polyimide as a matrix to provide a chain support; using dianhydride and diamine as raw materials, wherein the dianhydride includes one or more of terephthalic dianhydride, phthalic dianhydride and maleic dianhydride, and the diamine includes one or more of p-phenylenediamine, diaminobenzene and diaminobenzimidazole;
[0033] In a dry reaction container, dianhydride and diamine monomers are respectively dissolved in N,N-dimethylformamide solvent, the monomer concentration is between 0.5-2.0 mol / L, and pyridine is added as a catalyst to carry out polymerization reaction.
[0034] When the dianhydride solution and the diamine solution are polymerized, the diamine solution is slowly added to the dianhydride solution under nitrogen protection, and stirred at the same time to promote uniform reaction of the substances, and the temperature is maintained between 200-250°C. Too high a temperature may cause side reactions or polymer degradation, while too low a temperature may result in incomplete reaction. During the reaction, the polymer chain gradually grows and the monomer concentration gradually decreases. After the reaction is completed, the reaction product is cooled to room temperature and presents a high-viscosity solution or gel state.
[0035] The reaction product is poured into a cold ethanol solvent to precipitate polyimide, and the reaction product is washed with the cold ethanol solvent for multiple times to remove any unreacted monomers or residual solvents, and then the product is dried by vacuum drying until a constant weight state is obtained to obtain a high molecular weight polyimide as a matrix material.
[0036] S2, dissolving polyimide in N,N-dimethylformamide solvent to obtain a polyimide solution; pre-crushing the synthesized high molecular weight polyimide, gradually adding it to the N,N-dimethylformamide solvent, and mixing the polyimide and the solvent with a magnetic stirrer in a low-speed stirring manner until the polymer is completely dissolved to obtain a polyimide solution;
[0037] During the stirring process, gently heat the mixture to keep the temperature between 40-60°C. Too high a temperature will cause polymer degradation. If not used immediately, the polyimide solution should be stored in a sealed container to avoid light and high temperature.
[0038] S3, select tannic acid as a cross-linking agent, dissolve tannic acid in deionized water to form a tannic acid solution, and slowly add it to the polyimide solution under stirring conditions to mix thoroughly; slowly add tannic acid powder to 100-200mL of deionized water in batches, use a magnetic stirrer, and continue stirring at a medium speed to make the tannic acid and deionized water fully contact, and carry out the dissolution process at room temperature for 10-30 minutes until the tannic acid is completely dissolved to form a clear tannic acid aqueous solution; while stirring, observe the transparency of the solution. If suspended particles or precipitation appear in the solution, it may be that the tannic acid is not completely dissolved. The dissolution can be assisted by appropriately increasing the stirring speed or slightly heating (not exceeding 50°C).
[0039] Under stirring conditions, slowly drop the tannic acid solution into the polyimide solution, use a pipette or dropper to control the speed of addition, and ensure that the reactants are fully mixed by slow addition to achieve a good cross-linking effect. During the dropwise addition process, continue to stir to fully mix the tannic acid solution and the polyimide solution, keep the temperature at room temperature, and mix for 30 minutes to 1 hour.
[0040] S4, cross-linking the polyimide solution with the tannic acid solution to form a product with a three-dimensional grid structure; adding a sodium hydroxide solvent dropwise to the fully mixed polyimide and tannic acid solution, and heating the mixed solution to 150-200° C. and keeping stirring to allow the reactants to fully contact and react, and the reaction time is 2-4 hours;
[0041] Under the conditions of heating and stirring, the tannic acid molecules react with the functional groups on the polyimide chains to form cross-linked bonds, which connect the polyimide chains together to form a three-dimensional network structure.
[0042] S5. After the reaction is completed, the product is post-treated, the product is washed to remove unreacted tannic acid and solvent, and then dried to obtain the final polyimide adhesive.
[0043] After the cross-linking reaction reaches a predetermined degree, the reaction container is moved from the heating source to room temperature, the reaction is stopped by lowering the temperature, and after the temperature is lowered to room temperature, the stirring is stopped to obtain a polyimide gel product;
[0044] The cross-linked polyimide gel is washed with ethanol to remove unreacted tannic acid, catalyst and other impurities. During the washing process, ethanol is added to the container to completely immerse the product, and gently stirred with a glass rod or a magnetic stirrer to allow the solvent to fully contact the polyimide surface. The washing time is 30 minutes to 1 hour, and the washing is repeated 2-3 times until the pH value or color of the washing liquid is close to neutral, and then the solid is separated from the washing liquid using filter paper or cloth;
[0045] The washed polyimide product is transferred to a drying container and vacuum dried to improve the drying efficiency and prevent oxidation or other chemical degradation, thereby obtaining a final polyimide adhesive.
[0046] From the above, it can be seen that the high molecular weight polyimide synthesized as a matrix material through the polymerization reaction of dianhydride and diamine provides good mechanical strength and toughness. The three-dimensional network structure formed by the associated reaction significantly enhances the strength and rigidity of the material and improves its tensile and compressive resistance.
[0047] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, as well as parameter values (e.g., temperature, pressure, etc.), mounting arrangements, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure described herein that performs the function, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to several modifications still falling within the scope of the appended claims.
[0048] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.
[0049] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, without undue experimentation, the development effort will be a routine task of design, fabrication, and production.
[0050] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for synthesizing a high-performance polyimide binder with a three-dimensional network structure, characterized in that: The following steps are involved: S1, preparing a high molecular weight polyimide by reacting dianhydride and diamine, and using the polyimide as a matrix to provide a chain-like support; S2, dissolving polyimide in N,N-dimethylformamide solvent to obtain a polyimide solution; S3, selecting tannic acid as a cross-linking agent, dissolving the tannic acid in deionized water to form a tannic acid solution, and slowly adding the solution to the polyimide solution under stirring to fully mix; S4, cross-linking the polyimide solution with the tannic acid solution to form a product with a three-dimensional grid structure; S5. After the reaction is completed, the product is post-treated, the product is washed to remove unreacted tannic acid and solvent, and then dried to obtain the final polyimide adhesive.
2. The method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure as claimed in claim 1, characterized in that: In the step S1, dianhydride and diamine are used as raw materials, wherein the dianhydride includes one or more of terephthalic dianhydride, phthalic dianhydride and maleic dianhydride, and the diamine includes one or more of p-phenylenediamine, diaminobenzene and diaminobenzimidazole; In a dry reaction container, dianhydride and diamine monomers are respectively dissolved in N,N-dimethylformamide solvent, the monomer concentration is between 0.5-2.0 mol / L, and pyridine is added as a catalyst to carry out polymerization reaction.
3. The method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure as claimed in claim 2, characterized in that: When the dianhydride solution and the diamine solution are subjected to polymerization reaction, the diamine solution is slowly added to the dianhydride solution under nitrogen protection, while stirring, and the temperature is maintained between 200-250° C. During the reaction, the polymer chain gradually grows, and the monomer concentration gradually decreases. After the reaction is completed, the solution is cooled to room temperature, and the obtained reaction product presents a high-viscosity solution or gel state; The reaction product is poured into a cold ethanol solvent to precipitate polyimide, and the reaction product is washed with the cold ethanol solvent for multiple times to remove any unreacted monomers or residual solvents, and then the product is dried by vacuum drying until a constant weight state is obtained to obtain a high molecular weight polyimide as a matrix material.
4. The method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure as claimed in claim 1, characterized in that: In the step S2, the synthesized high molecular weight polyimide is pre-crushed and gradually added into an N,N-dimethylformamide solvent, and the polyimide and the solvent are mixed by stirring at a low speed using a magnetic stirrer until the polymer is completely dissolved to obtain a polyimide solution; During the stirring process, gentle heating is carried out and the temperature is maintained between 40-60°C.
5. The method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure as claimed in claim 1, characterized in that: In the step S3, the tannic acid powder is slowly added to 100-200 mL of deionized water in batches, and a magnetic stirrer is used to continuously stir at a medium speed to allow the tannic acid to fully contact the deionized water, and the dissolution process is carried out at room temperature for 10-30 minutes until the tannic acid is completely dissolved to form a clear tannic acid aqueous solution; Under stirring conditions, slowly add the tannic acid solution to the polyimide solution, use a pipette or dropper to control the addition speed, and continue stirring during the addition process to fully mix the tannic acid solution and the polyimide solution. Keep the temperature at room temperature and the mixing time is 30 minutes to 1 hour.
6. The method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure as claimed in claim 1, characterized in that: In the step S4, sodium hydroxide solvent is added dropwise to the fully mixed polyimide and tannic acid solution, and the mixed solution is heated to 150-200° C. and stirred to allow the reactants to fully contact and react, and the reaction time is 2-4 hours; Under the conditions of heating and stirring, the tannic acid molecules react with the functional groups on the polyimide chains to form cross-linked bonds, which connect the polyimide chains together to form a three-dimensional network structure.
7. The method for synthesizing a high-performance polyimide adhesive with a three-dimensional network structure as claimed in claim 1, characterized in that: In the step S5, after the cross-linking reaction reaches a predetermined degree, the reaction container is moved from the heating source to room temperature, the reaction is stopped by lowering the temperature, and after the temperature is lowered to room temperature, the stirring is stopped to obtain a polyimide gel product; The cross-linked polyimide gel is washed with ethanol to remove unreacted tannic acid, catalyst and other impurities. During the washing process, ethanol is added to the container to completely immerse the product, and gently stirred with a glass rod or a magnetic stirrer to allow the solvent to fully contact the polyimide surface. The washing time is 30 minutes to 1 hour, and the washing is repeated 2-3 times until the pH value or color of the washing solution is close to neutral; The washed polyimide product is transferred to a drying container and vacuum dried to obtain a final polyimide adhesive.